Penggunaan Media Pembelajaran Matakuliah Isyarat Visual Di Unimar Amni Semarang - Iwan Mahendro; Renny Hermawati (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2023)
Today's technology is experiencing very rapid development, technological development is not only in hardware but also in software. In the world of education also can not be separated from the use of technology. Formerly a teacher in teaching used the blackboard to explain learning material, with the development of technology today there are many kinds of learning media. The purpose of this study was to determine the response of cadets in the use of instructional media in Visual Cues courses. The benefits that can be obtained for lecturers can provide alternative learning media in conducting lectures. The results of this study are obtained a very good response from cadets because they have new experience in lectures on the Visual Signals course